2020
DOI: 10.1002/esp.4933
|View full text |Cite
|
Sign up to set email alerts
|

A seismic monitoring approach to detect and quantify river sediment mobilization by steelhead redd‐building activity

Abstract: The role of spawning salmonids in altering river bed morphology and sediment transport is significant, yet poorly understood. This is due, in large part, to limitations in monitoring the redd‐building process in a continuous and spatially extended way. A complementary approach may be provided through the use of a small seismic sensor network analysing the ground motion signals generated by the agitation of sediment during the redd‐building process. We successfully tested the viability of this approach by detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Hassan et al (2008) separated bedload transport due to Salmonidae spawning because this occurred at discharges well below those required for fluvial entrainment of sediment. Seismic signals (Dietze et al, 2020) and the disturbance of markers (Rice et al, 2019), tagged particles (Gottesfeld et al, 2004) and characteristic sediment (De Nadaï‐Monoury et al, 2013) have also been used to measure bioturbation in situ in rivers (for benthic organisms see the review, Maire et al, 2008). Upscaling the effects of biostabilization is more difficult because it requires a measure of how much sediment would have moved in the absence of biology.…”
Section: Scale and Guidelines For Future Researchmentioning
confidence: 99%
“…Hassan et al (2008) separated bedload transport due to Salmonidae spawning because this occurred at discharges well below those required for fluvial entrainment of sediment. Seismic signals (Dietze et al, 2020) and the disturbance of markers (Rice et al, 2019), tagged particles (Gottesfeld et al, 2004) and characteristic sediment (De Nadaï‐Monoury et al, 2013) have also been used to measure bioturbation in situ in rivers (for benthic organisms see the review, Maire et al, 2008). Upscaling the effects of biostabilization is more difficult because it requires a measure of how much sediment would have moved in the absence of biology.…”
Section: Scale and Guidelines For Future Researchmentioning
confidence: 99%
“…Because the majority of the gravel movement occurred from the central section toward the downstream section, maintenance such as raking gravel from the downstream section to the central section may increase the longevity of gravel patches. While this study represents one of the first to measure sediment transport in artificial spawning habitat, previous work has documented varying degrees of gravel movement for numerous other species in natural spawning habitat (Dietze et al, 2020; Gottesfeld et al, 2004, 2008; Hassan et al, 2008). Also, both mean burial depth and travel distance of tagged tracer substrate have been found to increase with increasing numbers of spawning individuals (Gottesfeld et al, 2004, 2008; Hassan et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Transport of spawning substrate in streams is, in large part, a result of high water velocities and turbulence during disturbance events such as floods (Gottesfeld, Hassan, Tunnicliffe, & Poirier, 2004; Kondolf, Vick, & Ramirez, 1996; Macdonald, King, & Herunter, 2010), but the extent of sediment transport is also shaped by spawning activities of fish. By excavating streambeds, salmonids move substrate downstream and change the streambed morphology (Dietze et al, 2020; Montgomery, Buffington, Peterson, Schuett‐Hames, & Quinn, 1996). Several studies have concluded sediment transport attributable to spawning salmonids to be comparable with, or even greater than, sediment transport associated with flood events (Gottesfeld, Hassan, & Tunnicliffe, 2008; Hassan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dietze et al ( 2020 ) quantified, for the first time, the timing, duration and energy transfer of redd building by spawning salmonids using environmental seismological approaches. They employed a small and easy‐to‐handle acoustic sensor network to record the ground motion of sediment agitation along a second‐order stream in the Cascade Mountain Range, NW USA.…”
Section: A Brief Overview Of Special Issue Contributionsmentioning
confidence: 99%